2019
DOI: 10.1017/laq.2018.78
|View full text |Cite
|
Sign up to set email alerts
|

Early Coastal Fiber Technology from the Caleta Vitor Archaeological Complex in Northern Chile

Abstract: The marine subsistence economy of the prehistoric people of northern Chile was heavily reliant on fiber technology for the components of nets, lines, and tethers. Despite the significance and the remarkable preservation of fiber artifacts along the arid Atacama coastline, these components have received little direct attention. This case study of fiber artifacts from the Caleta Vitor archaeological complex is the first broad overview of techniques, material usage/preference, and fiber-processing conventions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Significantly, a fully striped unku is featured in Guaman Poma de Ayala's (Guaman Poma de Ayala et al 1980Ayala et al [1615) illustration of a provincial administrator (Hughes 2010:Figure 12). Such stripes are also found on textiles from the Formative through the Late periods at Arica and Caleta Vitor (Agüero 2000;Horta 2004;Martens and Cameron 2019;Ulloa 2008). This does not imply that the CV unku was made locally, however.…”
Section: Discussionmentioning
confidence: 87%
“…Significantly, a fully striped unku is featured in Guaman Poma de Ayala's (Guaman Poma de Ayala et al 1980Ayala et al [1615) illustration of a provincial administrator (Hughes 2010:Figure 12). Such stripes are also found on textiles from the Formative through the Late periods at Arica and Caleta Vitor (Agüero 2000;Horta 2004;Martens and Cameron 2019;Ulloa 2008). This does not imply that the CV unku was made locally, however.…”
Section: Discussionmentioning
confidence: 87%
“…This highly productive ecosystem, coupled with terrestrial resources yielded by the wetland provides an abundance and variety of terrestrial and marine fauna and flora, all within the context of an extreme hyperarid environment (Herreros 2011;Fariña and Camaño 2012;Hernández et al 2014;González and Molina 2017;Latorre et al 2017). Interdisciplinary analyses of Caleta Vitor shell middens show long-term subsistence systems and socio-cultural structures based on terrestrial and maritime resources since the beginning of human occupation early in the Holocene (Roberts et al 2013;Carter 2016;Disspain et al 2016b;Santoro et al 2017;Martens and Cameron 2019;Santoro et al 2020).…”
Section: Recovery Methods Of Fish Remains In Caleta Vitormentioning
confidence: 99%
“…The earliest archaeological evidence of fibre technology is present in the Middle Holocene occupations in Caleta Vitor 1, where use of vegetal and animal raw materials for producing fibres have been identified. In CV3, indirect evidence from a shell bead from an Early Holocene layer and large amounts of small fish support the idea of cordage and fishing nets, respectively (Carter 2016;Martens and Cameron 2019). Additionally, Disspain et al (2016b) have suggested the use of nets since the Early Holocene due to the presence of Sciaenidae, a fish family that can be easily caught using nets due to their proximity to the shoreline.…”
Section: Big Fish or Small Fish?mentioning
confidence: 99%
See 2 more Smart Citations